2016
DOI: 10.21465/2016-sp-192-04
|View full text |Cite
|
Sign up to set email alerts
|

Korištenje interneta u starijoj dobi: je li važno za uspješno starenje?

Abstract: Internet predstavlja široku arenu mogućnosti u kojoj starije osobe mogu dobiti adekvatnu socijalnu potporu. Strana istraživanja jasno pokazuju da IKT pomaže starijima u održavanju komunikacije s članovima obitelji i prijateljima te da može pomoći i u održavanju psihofizičkog zdravlja. Kako je uspješno starenje višedimenzionalni konstrukt koji uključuje brojne determinante, poput učenja novih stvari, tako korištenje interneta može biti važan čimbenik bolje prilagodbe promjenama koje starenje donosi. Stoga je ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
2
13
0
2
Order By: Relevance
“…The reasons for this are found in the method of sampling, where the characteristics of the place of residence, the achieved level of mental and physical health and the level of education were considered differently. The results of this research also showed that more frequent use of the Internet is more common among older population with a higher level of education and their lower chronological and subjective age, as well as with better mental and physical health [12].…”
Section: The Use Of Computer Technology and The Internet Among The El...supporting
confidence: 52%
See 4 more Smart Citations
“…The reasons for this are found in the method of sampling, where the characteristics of the place of residence, the achieved level of mental and physical health and the level of education were considered differently. The results of this research also showed that more frequent use of the Internet is more common among older population with a higher level of education and their lower chronological and subjective age, as well as with better mental and physical health [12].…”
Section: The Use Of Computer Technology and The Internet Among The El...supporting
confidence: 52%
“…In comparison to the total number of Internet users, 61,7% have a Facebook profile and 15% an Instagram profile. Similarly, research by Nekić et al showed that Internet users most often accessed the Internet because of reading news and other interesting things on portals, then because of conversations with relatives and friends, use of social networks such as Facebook (21,8%), playing video games (2,5%) or due to work (1,7%) [12].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations